Preserving Semantics in Automatically Created Ontology Alignments - Orsi, G; Tanca, L (2010)
In an open world such as the Internet, one of the most challenging tasks is ontology alignment, which is the process of finding relationships among their elements. Performing this work in an automated fashion is, however, subject to errors, because of the different semantics carried by the same concept in different application domains or because of different ontology design styles which often produce incompatible ontology structures. In this chapter, we relate the most important approaches to ontology mapping revision, proposing a revision technique which aims at preserving the semantics of the original ontologies.